Society of Gynecologic Oncology Journal Club: Controversial conversations in gynecologic cancer - Navigating maintenance therapy for homologous recombinant proficient ovarian cancer - Whitney N. Goldsberry; Barbara S. Norquist; Rodney P. Rocconi; Susan C. Modesitt; Renata R. Urban (Elsevier, 2022)
The Society of Gynecologic Oncology (SGO) Journal Club is an open forum to review pertinent studies relevant to controversial topics in the management of gynecologic cancers. On August 3rd, 2022, SGO hosted a Journal Club focused on the role of maintenance therapy for homologous recombinant proficient (HRP) patients with ovarian cancer. Navigating optimal therapies has become more complex with the emergence of new clinical trial data and the evolving understanding of how to classify ovarian cancers as HRP. Our speakers, Drs. Susan Modesitt, Barbara Norquist and Rodney Rocconi presented Gynecologic Oncology Group (GOG) 218 (Burger et al., 2011), the VITAL Trial (Rocconi et al., 2021), and the PRIMA study (Gonzalez-Martin et al., 2019). We asked our experts to discuss their opinions and interpretations on the application of these data to current clinical practice. Poll questions were presented to the audience for a pre- and post-webinar comparison (Table 1). Results of the poll questions are shown in Table 1.